Comparison of Special Education Laws in the United States and Costa Rica: Provisions for Students with Disruptive Behavior - Ochoa, Theresa A. (2019)
This article compares special education laws in the United States and Costa Rica, highlighting services for students with disabilities who also manifest disruptive classroom behavior. Each country’s disability laws are described with a focus on the procedures used to discipline students with disabilities in public schools and the education services provided to juveniles suspended or expelled from public schools and/or incarcerated in juvenile facilities.